Impact of immunochemotherapy with R‐bendamustine or R‐CHOP for treatment naïve advanced‐stage follicular lymphoma: A subset analysis of the FOLL12 trial by Fondazione Italiana Linfomi - Nizzoli, Maria E.; Manni, Martina; Ghiggi, Chiara; Pulsoni, Alessandro; Musuraca, Gerardo; Merli, Michele; Califano, Catello; Bari, Alessia; Massaia, Massimo; Conconi, Annarita; Musto, Pellegrino; Mannina, Donato; et al. (Hematological oncology, 2023)
We conducted a post hoc analysis of the FOLL12 trial to determine the impact of different initial immunochemotherapy (ICT) regimens on patient outcomes. Patients were selected from the FOLL12 trial, which included adults with stage II–IV follicular lymphoma (FL) grade 1–3a and high tumor burden. Patients were randomized 1:1 to receive either standard ICT followed by rituximab maintenance (RM) or the same ICT followed by a response‐adapted approach. ICT consisted of rituximab‐bendamustine (RB) or rituximab, cyclophosphamide, doxorubicin, and prednisone (R‐CHOP), per physician's decision. A total of 786 patients were included in this analysis, 341 of whom received RB and 445 R‐CHOP. RB was more frequently prescribed to older subjects, females, patients without bulky disease, and those with grade 1–2 FL. After a median of 56 months of follow‐up, R‐CHOP and RB had similar progression‐free survival (PFS) (Hazard Ratio for RB 1.11, 95% CI 0.87–1.42, p = 0.392). Standard RM was associated with improved PFS compared to response‐adapted management both after R‐CHOP and RB. Grade 3–4 hematologic adverse events were more frequent with R‐CHOP during induction treatment and more frequent with RB during RM. Grade 3–4 infections were more frequent with RB. RB was also associated with a higher incidence of transformed FL. R‐CHOP and RB showed similar activity and efficacy, but with different safety profiles and long‐term events, suggesting that the treating physician should carefully select the most appropriate chemotherapy regimen for each patient based on patient's individual characteristics, choices, and risk profile.